Application of image processing in traffic control system & license plate detection - Islam, Aminul; Ahmed, Nafiz; Hasnain, Toaha; Tabassum, Iffat (BRAC Univeristy, 2017)
This thesis report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2017.